Radiation Oncologists’ Approach to Rectosigmoid Junction Tumors in Turkey: The Turkish Society for Radiation Oncology Gastrointestinal Group Survey Study (TROD 02-007) - Aynacı, Özlem; Serdar, Lasif; Canyılmaz, Emine; Hürmüz, Pervin (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The objective was to determine the preferences and perspectives regarding preoperative evaluation and treatment strategies for rectosigmoid junction cancer among radiation oncologists using a questionnaire survey. Materials and Methods: Since defining the correct origin of the neoplasm is essential in tailoring the most appropriate treatment scheme in the rectosigmoid junction region, we surveyed Turkish radiation oncologists about clinical decisions in rectosigmoid junction cancer patients via a 20-point questionnaire. Results: Based on responses from 130 radiation oncologists surveyed across the country, 119 (91.5%) used the anterior peritoneal reflection as the landmark, while 111 (85.4%) used the distance from the anal verge to the boundary between the rectum and sigmoid. This indicates that most of the participants decided to consider both pretreatment evaluation methods. Although distance at colonoscopy can be very variable, when the discrepancy was observed between these methods, 66 (50.8%) participants made the final decision according to the distance from the anal verge in our questionnaire. The conclusion from the questionnaire is that there is difficulty in interpreting magnetic resonance imaging findings, and there is a need for anatomic landmarks relevant to the limit between the rectum and sigmoid so that clinicians can confidently facilitate the diagnosis. Conclusions: There is a wide variation in the diagnosis and decision-making of rectosigmoid junction cancer among radiation oncologists in Turkey, according to our survey, because of several definitions of the rectosigmoid junction boundaries. Considerable attention is required to clarify whether the first preoperative treatment or surgery for rectosigmoid junction cancer. Cite this article as: Aynacı Ö, Serdar L, Canyılmaz E, Hürmüz P. Radiation oncologists’ approach to rectosigmoid junction tumors in Turkey: The Turkish society for radiation oncology gastrointestinal group survey study (TROD 02-007). Turk J Gastroenterol. 2023;34(9):911-917.